The creation of a competitive advantage in the portuguese cork industry: the contribution of an industrial district - Branco, Amélia (2011)
During the second half of the twentieth century, the Spanish cork industry had lost its hegemonic position to Portugal, in the world market of manufactured cork. In this work we intend to demonstrate that one of the most important explanations of the consolidation of this country's leadership in the cork business lies in the formation and development of the industrial cork district of Aveiro (Santa Maria da Feira) in the north of Portugal. It was there where the growth of the Portuguese stopper industry took place and with this, the decisive orientation of this nation towards the manufacture of natural cork, substituting the traditional Portuguese trade in cork planks. We argue that the legislation that established the control of the industrial investment in Portugal, the so-called Industrial Conditioning {Condicionamento Industrial) did not restrict the opening of small cottage industries in the north, that fact being a determining reinforcement of the competitiveness of Aveiro in the world stopper trade. Another measure of major importance was the wage regulation covering this industry, being responsible for the wage differential favourable to the north comparing with the south and the centre of the country. Finally, we highlight the role of a big company (Amorim&Irmaos) in the formation and development of this industrial district, which became a leader firm in this sector at a world-wide level.